2011
DOI: 10.1097/brs.0b013e3182191e13
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Intensive Functional Restoration Versus Outpatient Active Physiotherapy in Chronic Low Back Pain

Abstract: Both programs are efficient in reducing disability and sick-leave days. The FRP is significantly more effective in reducing sick-leave days. Further analysis is required to determine if this overweighs the difference in costs of both programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 46 publications
1
51
0
1
Order By: Relevance
“…Despite minor improvements in case 1's Biering Sorensen results, Previous studies have demonstrated improvements in the Biering Sorensen of 56.9 secs at one year follow up with 'functional restoration' training incorporating aerobic and resistance exercise for 5 weeks in back pain patients [13]. Few studies have followed trunk muscle endurance over an entire year, however studies of shorter durations have found increases in the Biering Sorensen ranging from 30.34% to 46.95% [14,15].…”
Section: Casementioning
confidence: 97%
“…Despite minor improvements in case 1's Biering Sorensen results, Previous studies have demonstrated improvements in the Biering Sorensen of 56.9 secs at one year follow up with 'functional restoration' training incorporating aerobic and resistance exercise for 5 weeks in back pain patients [13]. Few studies have followed trunk muscle endurance over an entire year, however studies of shorter durations have found increases in the Biering Sorensen ranging from 30.34% to 46.95% [14,15].…”
Section: Casementioning
confidence: 97%
“…Exercise-based interventions were used in all five studies, with one study47 also making ergonomic modifications, which comprised postural retraining. While two studies44 45 reported significant reductions in sick leave following functional rehabilitation interventions compared to other therapies, three studies43 46 47 reported no significant effect compared with individual physiotherapy, exercise therapy or ergonomic training. The quality of evidence for the outcome of sick leave was assessed as low.…”
Section: Resultsmentioning
confidence: 99%
“…The specific program descriptions of its procedures has been published in multiple outcome studies documenting its effectiveness in providing functional improvement, often cited in national treatment guideline references. 8, 9, 25–32 The effectiveness of functional restoration methods have also been well documented in the literature. 33–41 …”
Section: Methodsmentioning
confidence: 99%